Paranhos spring galleries catchworks from Porto urban area (NW Portugal) : a geoenvironmental approach - Chaminé, Helder I. (2005)
This multidisciplinary study presents the preliminary results of the structural geology and geotechnical studies of a granitic rock-mass block delimitation. In addition, hydrogeological and ecotoxicological methods were used to assess the nature and suitability for use of groundwater from spring horizontal galleries catchworks located in Porto urban area. These springs represented one of the main water supplies of Porto city, for more than five centuries. For the characterisation of the granitic rock-mass, the scanline sampling technique of discontinuities has been applied to the study of granitic free rock-mass faces from Paranhos tunnels (Porto urban area). For that purpose, the underground area (ca. 3km extension and a -25m of depth) was studied using the following tools: subsurface geological and geotechnical mapping (scale: 1/1.000), structural geology and geotechnics/geomechanics techniques. Water samples were collected from several sampling sites for hydrogeological and ecotoxicological analyses. A geoenvironmental approach probably offers the best potential for reliable surface water and groundwater studies and characterisation of the geospatial parameters variability, such as, lithological heterogeneity, structural geology features, geomorphology, hydrogeology and geotechnics of a specific site. This study contributes to a better water management of the urban geo-space, either in historical and heritage terms, or for several purposes of public use.